2019
DOI: 10.7150/ijbs.30499
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipidomic Analysis of C. elegans reveals Development- and Environment-dependent Metabolic Features

Abstract: Sphingolipids (SLs) serve as structural and signaling molecules in regulating various cellular events and growth. Given that SLs contain various bioactive species possessing distinct roles, quantitative analysis of sphingolipidome is essential for elucidating their differential requirement during development. Herein we developed a comprehensive sphingolipidomic profiling approach using liquid chromatography-mass spectrometry coupled with multiple reaction monitoring mode (LC-MS-MRM). SL profiling of C. elegans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…Inspection of ESI-(À )-HR-MS e spectra also confirmed that the [ 13 C 5 ]-labels are exclusively located in the homologous N-iso-acyl building blocks. Taken together, these results demonstrate that the biogenesis of N-iso-acyl substituted ceramides 18 (R' = CH 3 ) in wildtype C. elegans incorporates two L-leucine (12) units in the d17 : 1iso sphingosine (17) and N-iso-acyl moieties, respectively, and further indicates that these two iso-acyl building blocks are derived from two distinct biosynthetic pathways, the daf-22 dependent de novo biogenesis of d17 : 1iso sphingosine ( 17) and the daf-22 independent lipogenesis of very long chain iso-fatty acids (Scheme 2).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Inspection of ESI-(À )-HR-MS e spectra also confirmed that the [ 13 C 5 ]-labels are exclusively located in the homologous N-iso-acyl building blocks. Taken together, these results demonstrate that the biogenesis of N-iso-acyl substituted ceramides 18 (R' = CH 3 ) in wildtype C. elegans incorporates two L-leucine (12) units in the d17 : 1iso sphingosine (17) and N-iso-acyl moieties, respectively, and further indicates that these two iso-acyl building blocks are derived from two distinct biosynthetic pathways, the daf-22 dependent de novo biogenesis of d17 : 1iso sphingosine ( 17) and the daf-22 independent lipogenesis of very long chain iso-fatty acids (Scheme 2).…”
Section: Resultssupporting
confidence: 53%
“…[16,29,30,49] Isomeric structures were assigned based on the incorporation of branchedchain amino acids (BCAA). A total of 48 ceramides 18 were identified, which constitute a homologous series characterized by a conserved d17 : 1iso sphingosine (17) backbone that is N-acylated with straight and isobranched acyl and 2-hydroxy-acyl moieties ranging from 16 to 27 carbons (Figure 1,a -1,c, Tables S1 and S2). C. elegans' ceramides are dominated by Cer d17 : 1iso/22:0(2OH) (18, n = 3, R' = H, X=OH) with a N-(2-hydroxy)docosanoyl moiety.…”
Section: Resultsmentioning
confidence: 99%
“…We note that our protocol called for thawing frozen samples prior to lipidomics sample preparation. This freeze and thaw have been previously done on C. elegans for lipidomics [ 36 , 85 ], and our quality control does not suggest degradation of any particular class of lipids. However, others have prepped from frozen C. elegans extracts directly [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although they appear to be much less common than unbranched LCBs, branched sphingolipids can still be found across kingdoms. For example, C17 methyl-branched LCBs are produced by Sphingobacterium species [31] and Caenorhabditis elegans [83, 84], whereas a C19 methyl-branched LCB is produced by a marine strain of the fungus Aspergillus niger [85]. Iso- and anteiso-branched fatty acids do occur in Nostoc and Anabaena species [86].…”
Section: Discussionmentioning
confidence: 99%